2020
DOI: 10.1055/s-0040-1702924
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Amniotomy Associated with Higher Likelihood of Vaginal Birth after Cesarean?

Abstract: Objective The study aims to reduce cesarean rates, eligible women are being offered an option of vaginal birth after cesarean (VBAC). However, little data exist regarding efficacy of amniotomy as a tool in this population. We sought to evaluate the impact of early amniotomy on VBAC success. Study Design This is a secondary analysis case-control study using the MFMU (Maternal-Fetal Medicine Units Network) Cesarean Registry. Women were included if they had a singleton pregnancy, were attempting VBAC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recently published case–control secondary analysis of the MFMU (Maternal–Fetal Medicine Units Network) Cesarean Registry compared the prevalence of early AROM (4 < cm) in women with a successful vs failed TOLAC. They found that early AROM was associated with a 34% decrease in VBAC success ( p < 0.01) with no higher rates of chorioamnionitis [ 19 ]. However, our study only includes women with early AROM, limiting the relevance of the MFMU study to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published case–control secondary analysis of the MFMU (Maternal–Fetal Medicine Units Network) Cesarean Registry compared the prevalence of early AROM (4 < cm) in women with a successful vs failed TOLAC. They found that early AROM was associated with a 34% decrease in VBAC success ( p < 0.01) with no higher rates of chorioamnionitis [ 19 ]. However, our study only includes women with early AROM, limiting the relevance of the MFMU study to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pasko et al published a retrospective cohort study of patients with obesity indicating that early amniotomy is associated with a higher risk of cesarean delivery [8]. Similarly, Varvoutis et al published a case-control study using a large network cesarean registry and found that early amniotomy was not associated with higher rates of vaginal birth after cesarean [9]. One subpopulation where benefit of early amniotomy is less clear are patients who have low cervical This article is protected by copyright.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, for some subpopulations the impact of early amniotomy is less clear. [8][9][10] Pasko et al published a retrospective cohort study of patients with obesity indicating that early amniotomy is associated with a higher risk of cesarean delivery. 8 Similarly, Varvoutis et al published a case-control study using a large network cesarean registry and found that early amniotomy was not associated with higher rates of vaginal birth after cesarean.…”
mentioning
confidence: 99%
See 1 more Smart Citation